Characterization of the intestinal microbiome in eutrophic, obese omnivores, and vegetarians - Polo, Tatiana Cristina Figueira [UNESP]; de Ré Lai, Mariana Righetto [UNESP]; Miot, Hélio Amante [UNESP] (Springer Nature, 2022)
Purpose: To characterize the intestinal microbiome (IM) of omnivores (obese or eutrophic) and vegetarians and correlate them with their nutritional profile in a Brazilian adult male sample. Method: Cross-sectional study involving 21 adult males: eutrophic omnivores (EuOn), obese omnivores (ObOn), and eutrophic vegetarians (EuVeg). Demographic, anthropometric, and dietary data were assessed. The characterization of IM was carried out using stool samples (fecal microbiome) and subsequent metagenomic analysis (16S amplicon). Results: EuVeg had a higher fiber intake and more daily meals than the other groups, however, caloric, protein, and carbohydrate intake was higher among obese individuals. ObOn showed the lowest ecologic richness index; in addition to a greater Firmicutes/Bacteroidetes ratio. Two profiles of intestinal microbioma were identified that allowed the characterization of the groups. EuOn were mainly represented by the Christensenellaceae family and the Faecalibacterium prausnitzii species. EuVeg were represented by the Coriobacteriaceae family, and the Prevotella copri species. ObOn were represented by the Enterobacteriaceae family and by the Blautia producta species. Conclusion: Omnivorous (obese and eutrophic) and vegetarian men presented different patterns of IM according to the ecologic diversity and the ratio of Firmicutes/Bacteroidetes phyla. The patterns of IM were correlated with the nutrient composition of the diet, substantiating dietetic interventions for the modulation of IM.
Keywords: Diet; Gastrointestinal microbiome; Microbiota; Obesity; Vegetarian diet; Western diet